Application of Nanotechnology for Antibacterial Drug Delivery: A Review - Irayyif, Sajjad Mohsin; Qushawi, Alwan Al; Abdulridha, Reham Najem; Obaid, Aula Hassoon (American Journal of Biology and Natural Sciences, 2024)
Metal-based nanoparticles have been thoroughly examined for many biological purposes. The WHO states that metal-based nanomaterials have shown efficacy against prioritized pathogens besides diminutive size and specificity for microorganisms. The nanoparticles made from metals exhibit non-specific methods of bacterial toxic effects, as they do not interact with a particular receptor in bacterial cells. This characteristic complicates the development of bacterial resistance and expands the range of antibacterial efficacy. Consequently, most effectiveness studies on nanoparticles made from metals have shown encouraging outcomes against both Gram-positive and Gram-negative bacteria. This paper aims to thoroughly assess the current advancements in using significant metal nanoparticles as antibacterial agents. Particular attention is devoted to silver nanoparticles, but other nanoparticles often used in ant biotherapy, such as gold, zinc oxide, copper, and copper oxide, are also examined. This review’s originality stems from the comparative analysis of various metal nanoparticles, encompassing their manufacturing techniques, physicochemical characterization, pharmacology, and the toxicological risks associated with their application as antibiotics. Their role has been emphasized in advancing different, more vital pharmaceuticals aimed against multi-resistant different types of bacteria.